Pengaruh Financial Stability, External Pressure, Financial Target & Personal Financial Needs terhadap Financial Statement Fraud - Hemarizki, Ladya Cheryl; Wijaya, Trisnadi (Universitas Multi Data Palembang, 2024)
The purpose of this study was to test and analyze the relationship between financial stability, external pressure, financial targets & personal financial needs on financial statement fraud. This study uses secondary data, namely financial statements and annual reports. This study surveyed 62 manufacturing companies listed on the IDX between 2020-2022. The sampling technique used was purposive sampling. The research data were analyzed using multiple linear regression analysis. The results showed that financial stability & external pressure had a significant effect on financial statement fraud. Meanwhile, financial targets & personal financial needs have no effect on financial statement fraud.